Willow - Andrews, V. C. (Virginia C.) (New York : Pocket Books, 2002)
Stumbling upon some life-altering family secrets while reading her adoptive father's journal, Willow De Beers heads for Palm Beach to search for her birth family and stumbles upon the dark truth about her origins.
Keywords: Adopted children -- Family relationships -- Fiction; Rich people -- Fiction; Suspense fiction; Florida -- Fiction; Domestic fiction